Path loss prediction models for Corridor propagation at 24GHz - Femi_Jemilohun, Oladunni Juliet; Femi-Jemilohun, Oladunni Juliet; Walker, Stuart D (Discoveries in Agriculture and Food Sciences, 2014)
Mm-wave bands have recently become major options for short-range, high speed communication systems especially in the indoor wireless local area networks (WLANs). The pathloss prediction model is one of the metric parameters for determining the system effectiveness and performance in wireless indoor propagation. The channel characterization of 24GHz band in corridor propagation through extensive field strength measurements in real time application was conducted in this work. The results were used to derive the path loss equation for corridor propagation at this spectrum band based on log-distance path loss model and log-normal shadowing model. The pathloss realized falls within the estimated values in such scenario, it is therefore concluded that the predicted mathematical model for the described environment is accurate. Also the predicted pathloss which is lower than the free space propagation path loss results in aggregate high data rate, hence improved system performance is achieved.